1991
DOI: 10.1007/bf02565126
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in bone metabolism in young healthy subjects

Abstract: Serum vitamin D metabolites and urinary calcium excretion; parameters of bone formation (serum alkaline phosphatase, serum osteocalcin); parameters of bone resorption (24 hour hydroxyprolinuria, 2 hour fasting urinary hydroxyproline/creatinine ratio); and parameters of cortical and trabecular bone density, parathyroid hormone (iPTH, COOH terminal assay), and serum minerals (calcium, phosphorus) were followed serially in 55 young adults (21 women and 34 men) from December 1985 until January 1987 at four differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 38 publications
8
33
1
Order By: Relevance
“…Maintenance of serum calcium can be made by bone mineralization andaor increased loss. As shown in Table 3, 24 h urinary excretion was enhanced during summertime thereby conÂźrming previous studies on the inÂŻuence of season on urinary calcium excretion (Robertson et al, 1974;Vanderschueren et al, 1991). Phosphorus excretion resembled that of calcium with higher values in summer and lower in winter (Table 3).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Maintenance of serum calcium can be made by bone mineralization andaor increased loss. As shown in Table 3, 24 h urinary excretion was enhanced during summertime thereby conÂźrming previous studies on the inÂŻuence of season on urinary calcium excretion (Robertson et al, 1974;Vanderschueren et al, 1991). Phosphorus excretion resembled that of calcium with higher values in summer and lower in winter (Table 3).…”
Section: Discussionsupporting
confidence: 86%
“…Variations in serum 25OHD and urinary calcium secretion but no change in alkaline phosphatase, serumosteocalcin (biomarkers of bone formation) and urinary hydroxyproline (biomarker of bone resorption) have been observed in young males and females (Vanderschueren et al, 1991). A reduction in serum 25OHD of young subjects during wintertime has been found in several studies in western and northern Europe (McKenna, 1992).…”
Section: Introductionmentioning
confidence: 97%
“…Seasonal variation of bone mineral density, bone mineral content and bone size Earlier studies have reported seasonal variation in bone mass in different populations (Bergstralh et al 1990;Dawson-Hughes & Harris, 1993;Rosen et al 1994;Rapuri et al 2002) but others have not found such a variation (Vanderschueren et al 1991;Tsai et al 1997;Overgaard et al 1998). We stated a 7·5 -8·2 % seasonal variation in site-specific BMD in early puberty girls, which seems to be somewhat higher than observed in healthy adults (Bergstralh et al 1990;Dawson-Hughes & Harris, 1993).…”
Section: Seasonal Variation In Serum 25-hydroxyvitamin D and Parathyrcontrasting
confidence: 51%
“…In separate groups, U-DPyr and U-Pyr did not follow the seasonal rhythm. In follow-up studies resorptive bone markers tend to increase during winter ( Vanderschueren, 1991;Rosen et al 1994;Woitge et al 2000;Rapuri et al 2002;Lehtonen-Veromaa et al 2002), due to increased parathyroid hormone secretion. Although S-iPTH increased throughout the winter among early puberty girls, we did not observe an increase in resorptive markers: the use of one time specimen to measure bone remodelling markers in a cross-sectional study is not informative, because of many confounding factors or due to a small sample size (e.g.…”
Section: Mechanism Of Seasonal Variation In Bone Mineral Densitymentioning
confidence: 99%
“…In samples collected during summer, we found a gradual increase in BMD of the total hip up to a S-25OHD level of 40 nmol L À1 (6% of the cohort). In women with S-25OHD concentrations below 30 nmol L À1 during summer, adjusted BMD was 11% lower [95% confidence interval (CI) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and in those with S-25OHD levels of 30-40 nmol L À1 BMD was 6% lower (95% CI 1-11), compared with women with S-25OHD levels above 80 nmol L…”
Section: Categories Of Vitamin D Status Were Determined By S-25ohd (Mmentioning
confidence: 99%